Hepatic perivascular epithelioid cell tumor: A case report - Rok Dežman; Dragan Mašulović; Peter Popovič (European Journal of Radiology Open, 2018)
Perivascular epithelioid cell tumor (PEComa) of liver is extremely rare hepatic neoplasm with only 30 cases reported in the literature. These lesions are found mainly in young females and may present a potential pitfall in the characterisation of focal liver lesions. The biological behavior of PEComa varies from generally benign to rarely malignant and metastatic disease. We report a case of a patient with hepatic PEComa with the corresponding imaging findings on the ultrasound, contrast-enhanced ultrasound (CEUS) and hepatospecific MRI. After failed attempt to characterize the lesion by percutaneous biopsy, surgical resection was conducted and the final diagnosis was achieved. Keywords: Perivascular epithelioid tumor, PECOM, Focal liver lesion, CEUS, MRI